PENGARUH HARGA MINYAK DUNIA, KESTABILAN POLITIK DAN SUKU BUNGA TERHADAP NILAI TUKAR DI INDONESIA - Hesniati Hesniati; Zulfiniar Nur Kalimah; Hadi Nanto; Yulianti Yulianti; Harsono Harsono (Universitas Madura, 2022)
This study discusses the relationship between world oil prices, political stability and interest rates on exchange rates in Indonesia which is analyzed using monthly time series data for 2010-2020 and processed using the E-Views application and tested with multiple linear regression. After research, it was found that world oil prices have a negative and significant effect on the exchange rate, political stability has a positive and significant effect on the exchange rate, while interest rates have no significant relationship with the exchange rate. Meanwhile, based on the results of the tests carried out, the variables of world oil prices, political stability and interest rates have a proportion of 56% in explaining the exchange rate as the dependent variable, while the remaining 44% is influenced by other variables outside of this research variable. Investors and international economic actors must be able to paying attention to world oil prices and political stability in predicting changes in exchange rates. The government as a policy maker have to maintain crude oil supplies, maintain political stability, and control interest rates to maintain exchange rates stability